Table of Content - - (Journal of Humanities & Social Sciences, 2024)
Table of Content: 1. Developing A Three-Dimensional Model of Khanaqin High lands by using Blender Program, Mount Bamu as an Example Ass-Prof. Ammar Hussein Mohammed 2. Craft sects in the city of Jeddah in the 14th century AH/20 AD Ms. Abeer Othman Al-Sabban 3. Qatar Charity’s role in providing relief to Syrian refugees during the winter of 2024 in Jordan Dr. Sahar Yousef Alsharo 4. The role of social counseling in facing the problems of widows and divorcees - A field study on the beneficiaries of Organization Girl albadayie .Saudi Arabia (1444-2023) – Ms. Feda Mohammed Alnwaiser 5. Social Compatibility and It is Relationship to Self-Confidence (An Applied Study on A Sample of Students at King Abdulaziz University in Jeddah Province) Mr. Mohammed Ahmed Almabadi 6. The role of nature reserves in sustainable ecotourism Imam Saud bin Abdul-Aziz Reserve (Mahazat Al-Sayd) Dr. Samah Rabah Alkuhaily